What should be the minimum frequency of micro testicular sperm extraction (m-TESE) in patients with Klinefelter syndrome? (Annals of Medical Research, 2021)
Aim: To investigate whether a second or even a third surgery is required for sperm retrieval in non-mosaic Klinefelter syndrome patients who underwent a successful/failed micro-testicular sperm extraction (m-TESE).Material and Methods: The patients underwent physical examination, genetic analyses, pathological screening between 2008 and 2018. In the patients, sperm retrieval rates, pregnancy after intracytoplasmic sperm injection (ICSI) and baby take-home rates were examined.Results: M-TESE was repeated for the second time in thirty-five patients in total, with twenty of that underwent their first m-TESE with a negative result and fifteen with a positive result. In =6/20 patients (30%) who had a negative result with the first m-TESE and in n=9/15 patients (60%) who had a positive result with the first m-TESE, sperm was detected the second time. Pregnancy was achieved in n=2/6 patients (33%) who were negative the first time and positive the second time. Baby take-home was achieved in one patient (16.6%). Conclusion: In addition to patients from whom sperm could be retrieved previously, sperm could be detected especially in the second and even third redo m-TESE in patients from whom sperm could not be retrieved. Pregnancy occurred and baby take-home was achieved. Despite the presence of a very limited testicular tissue, it is recommended for this procedure to be performed by expert practitioners upon discussing very openly the complications and achievements, to decide accordingly and repeat m-TESE in these patients where possible.
Keywords: Sperm; klinefelter; pregnancy